In search of interactive networks in care community and familiar of elderly: Building moments fed back to update the senses - de Lima, Laila Angélica; Albuquerque de Souza, Maria Antoniêta (Guará Journal, 2025)
he communication of research results implies the responsibility of the extension. The text describes two movements of returning of the survey with elderly caregivers: 1. deal with training processes in caregivers’ networks employees for communication and social interaction, 2. systematically observed in the joint reflection (seniors / caregivers / other neighborhood) of the subjects the effects of adherence of caregivers and seniors to sociability, described in this work. The methodology of Everyday Life Network (MARES) and action research facilitated the visibility of these exhilarating experiences to sociability, reflection and analysis of narratives produced effect of unification exposed suggesting ways of living
Keywords: Aging health; Social interaction; Caregivers